2011
DOI: 10.3109/01443615.2010.542516
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour in women with one previous caesarean section

Abstract: We conducted a postal survey of NHS obstetric consultants working in England regarding their own practice and views on induction of labour in women with one previous caesarean section. Out of 480 consultant obstetricians across England, 322 replied, giving a response rate of 67%. Our survey has revealed a wide variation in practice of consultants across England, regarding induction of labour at term or post-term in women with one previous caesarean section. Hence, we feel that there is a need for a national au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Since a previous cesarean section is often an exclusion criterion in randomized controlled trials (RCTs) on IOL, a recent Cochrane review was only able to include two RCTs involving a total of 80 women, which compared different methods of IOL, but not induced vs. spontaneous labor [6]. Therefore, it is not surprising that both Udayasankar et al [7] and Gupta et al [8], by performing a national survey, reported a wide variation in practice of IOL at term or postterm in women with a previous cesarean section.…”
Section: Introductionmentioning
confidence: 96%
“…Since a previous cesarean section is often an exclusion criterion in randomized controlled trials (RCTs) on IOL, a recent Cochrane review was only able to include two RCTs involving a total of 80 women, which compared different methods of IOL, but not induced vs. spontaneous labor [6]. Therefore, it is not surprising that both Udayasankar et al [7] and Gupta et al [8], by performing a national survey, reported a wide variation in practice of IOL at term or postterm in women with a previous cesarean section.…”
Section: Introductionmentioning
confidence: 96%
“…Comparison of the results of our study with surveys from the UK, Australia New Zealand, and Canada shows that the use of prostaglandins for cervical ripening in women with a prior cesarean delivery is by far the lowest in the Netherlands (20%) [1618]. Also, cervical ripening using mechanical methods in this group is much more popular in the Netherlands (73%) compared to England (3%) (Table 6).…”
Section: International Comparison Of Induction Of Labor In Women Wmentioning
confidence: 70%